Analisis Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (K3) - Amin, Jurisman; Bararah, Kirami (Tameh, 2021)
Along with the rapid pace of development of multi-storey building construction in indonesia, it creates a high risk of work accidents, especially for field, workers therefore the role of controlling the risk of woek accidents is compulsary. Poor implementation of occupational health and safety can damage the occupational health and safety management (OHSM) system in a construction project. So the problem is wich factors are dominant in the application of OHSM in the construction of the Bapelkes building and what is the level of application of OHSM in the construction project. This study aims to analyze the level of implementation of OHSM implementation in the construction of the Bapelkes building. This research method uses quantitative and qualitative approaches through interviews and distributing questionnaires to PT. The work of Mukti Bersaudara as many as 12 people. This study consisted of 9 variables. The result of the validity test of the mean value of r-count of each variable is 0.81 and the r-table value is 0.497, so it fulfills the requirements of r-count> r table. The result of the reliability test on each variable obtained an average value of 0.8 and Cronbach’s Alpha critical value of 0.6, wich is means all variables are declared reliable. The result of the descriptive analysis of the highest mean value were obtained in the factor of development and commitment maintenance (X1) with a value of 4.72, and the last order was obtained the variable (X2) with a value of 4.45. it can be concluded that the very dominant factor in implementing OHSM in Bapelkes building construction projects is the development and maintenance of commitment (X1). The implementation of OHSM in the construction of new dormitory and class building project for the National Health planning Agency (Bapelkes) has been implemented well-planned, measured, and structured, and properly integrated according to the PP. No. 5 of 2012 concerning the occupational health and safety management system, although it has not been fully implemented, it is obtained from the average percentage of application assesment, which is 92.0%